Coprecipitation of Organic Matter, Phosphate With Iron: Implications for Internal Loadings of Phosphorus in Algae-Dominated and Macrophyte-Dominated Lakes - Dai, JiaRu; Zhang, QiaoYing; Liu, JingJing; Wen, ShuaiLong; Zhang, YuFeng; He, Ding; Du, YingXun (Frontiers in Environmental Science, 2022)
Coprecipitation with iron (Fe) plays an essential role in the biogeochemical cycles of carbon (C) and phosphorus (P) in lakes. The sources and composition of organic matter (OM) mediate its association with Fe, which could thus influence the immobilization of phosphorus. In this study, water-soluble organic matter from the sediments of two typical types of shallow lakes, macrophyte-dominated zones (M-WSOM) and algae-dominated zones (A-WSOM) was extracted and the coprecipitation of WSOM, P with Fe (III) was investigated. The results showed that the coprecipitation process was enhanced with increasing Fe (III) or decreasing pH value. The presence of A-WSOM showed stronger inhibition on the coprecipitation of P than that by M-WSOM. The formed ternary coprecipitates with A-WSOM had lower C/Fe ratios (0.13–2.78) than those with M-WSOM (1.28–4.05). Because A-WSOM had lower aromaticity which resulted less coprecipitation with Fe (III) and more functional groups that could complex with Fe (III), thus resulting the less immobilization of organic carbon and P with A-WSOM. Our results demonstrated that in algae-dominated zones, more phosphorus could remain soluble during the ternary coprecipitation, and perform positive feedback with the growth of phytoplankton, providing a novel explanation for the difficulty of restoring the eutrophic lake.